TRANSFORMASI NILAI BUDAYA DARI SUMBER SEJARAH KE KARYA SASTRA KONTEMPORER - Moh. Ichsan (PT. Habe Cendekia Utama, 2025)
This research examines the transformation of cultural values from Indonesian historical sources to contemporary literature, where history and literature form a dialectic of national identity inheritance amidst post-Reformasi socio-political changes. The background of the problem includes an interdisciplinary gap in the digital reinterpretation of values such as heroism, religiosity, social hierarchy, patriarchy, loyalty, and custom, which have evolved from feudal legitimacy to contemporary critique, as seen in the works of Eka Kurniawan and Ayu Utami. The research aims to identify dominant values, forms of transformation (preservation, modification, deconstruction), authorial strategies, influencing factors, and mapping evolutionary patterns for a literary-historical study framework. The descriptive qualitative method uses thematic content analysis of 20 primary historical sources (the Kedukan Bukit inscription, the Javanese chronicle) and 15 contemporary novels (Lelaki Harimau, Saman), triangulated with interviews with 10 experts, NVivo codification, and pattern matching of KristevaDerrida theory based on Miles-Huberman (2014). The results show a dominant transformation of modification (45%) and deconstruction (25%), with the main factors being globalization (40%), author ideology (30%), and the demands of Gen Z readers (30%), changing the function of values from sacredlegitimacy to profane-social criticism, enriching literature as a bridge of hybrid identity in the digital era.